Analisis Penggabungan Korpus dari Hadits Nabi dan Alquran untuk Mesin Penerjemah Statistik - Hafidz Ardhi; Herry Sujaini; Arif Bijaksana Putra (Jurnal Linguistik Komputasional, 2018)
Each region has different language to communicate. A communication can run well if each other can understand the language that use in communication process. Machine translation is an automatic translation machine to translate a text from a language to another language. In the machine translation there will be an automatic evaluation. Automatic evaluation is needed to measure the quality of translation text from machine translation using automatic metric. The metric is use to determine score toward quality in various ways until get percentage at the final result. Evaluation of translation machine system using automatic metric is quick, easy and inexpensive way rather that human evaluation. BLUE is a common metric used by researcher to evaluate machine translation. For this research, researcher used Arabic Languange. Corpus that used are corpus of Al-quran, corpus of hadith, and combined corpus. The corpus will be tested with the type of sentence and 4 level numbers of sentences. The test will be done in two times. First, test without MADAMIRA. Second, test using MADAMIRA. The result of tested without MADAMIRA produce BLEU score for corpus of Al-quran in amount of 10,56%, corpus of hadith 27,65%, and combined corpus 15,41%. In the other hand, the result of tested corpus used MADAMIRA got result of BLEU for corpus of Al-quran 1,44%, corpus of hadith 32,90% and combined corpus 41,46%.